EXPLORING THE DIFFERENCES AND SIMILARITIES BETWEEN ENGLISH AND UZBEK FOLKLORE - Usmonova Sevara Sultanovna; Meliboyeva Nazokat Elyor kizi (TADQIQOTLAR.UZ, 2023)
This article aims to explore the differences and similarities between English and Uzbek folklore, shedding light on the distinct cultural expressions and oral traditions of these two rich heritage. By examining the themes, characters, storytelling techniques, and cultural influences present in each folklore, we gain a deeper understanding of the unique narratives that have shaped these communities. The comparative analysis presented in this article highlights the significance of folklore as a powerful medium for cultural preservation and transmission.